Dietary intervention improves metabolic levels in patients with type 2 diabetes through the gut microbiota: a systematic review and meta-analysis - Xu, Xiaoyu; Zhang, Fan; Ren, Jiajia; Zhang, Haimeng; Jing, Cuiqi; Wei, Muhong; Jiang, Yuhong; Xie, Hong (Frontiers in Nutrition, 2024)
Background: Poor dietary structure plays a pivotal role in the development and progression of type 2 diabetes and is closely associated with dysbiosis of the gut microbiota. Thus, the objective of this systematic review was to assess the impact of dietary interventions on improving gut microbiota and metabolic levels in patients with type 2 diabetes.We conducted a systematic review and meta-analysis following the PRISMA 2020 guidelines.Results: Twelve studies met the inclusion criteria. In comparison to baseline measurements, the highfiber diet produced substantial reductions in FBG (mean difference -1.15 mmol/L; 95% CI, -2.24 to -0.05; I2=94%; P=0.04), HbA1c (mean difference -0.99%; 95% CI, -1.93 to -0.03; I2=89%; P=0.04), and total cholesterol (mean difference -0.95 mmol/L; 95% CI, -1.57 to -0.33; I2=77%; P=0.003); the high-fat and low-carbohydrate diet led to a significant reduction in HbA1c (mean difference -0.98; 95% CI, -1.50 to -0.46; I2=0%; P=0.0002). Within the experimental group (recommended diets for type 2 diabetes), total cholesterol (mean difference -0.69 mmol/L; 95% CI, -1.27 to -0.10; I2=52%; P=0.02) and LDL-C (mean difference -0.45 mmol/L; 95% CI, -0.68 to -0.22; I2=0%; P<0.0001) experienced significant reductions in comparison to the control group (intervention diets). However, no statistically significant differences emerged in the case of FBG, HbA1c, HOMA-IR, and HDL-C between the experimental and control groups. The high dietary fiber diet triggered an augmented presence of shortchain fatty acid-producing bacteria in the intestines of individuals with T2DM. In addition, the highfat and low-carbohydrate diet resulted in a notable decrease in Bacteroides abundance while simultaneously increasing the relative abundance of Eubacterium. Compared to a specific dietary pattern, personalized diets appear to result in the production of a greater variety of beneficial bacteria in the gut, leading to more effective blood glucose control in T2D patients.T2D through modulation of the gut microbiota. Tailored dietary regimens appear to be more effective than standard diets in improving glucose metabolism. However, given the limited and highly heterogeneous nature of the current sample size, further well-designed and controlled intervention studies are warranted in the future.